Appearance of the first Associative Dictionary in the Romanian language space at the Scientific Library USARB (Confluenţe Bibliologice, 2023)
In this article, the first associative dictionary appears in the Romanian language: the history and methodology of the dictionary, the structure, the purpose and the destination of the dictionary.